2013
DOI: 10.1021/nn4002165
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Surfactant Structures on Length and Chirality Resolved (6,5) Single-Wall Carbon Nanotubes by Analytical Ultracentrifugation

Abstract: The structure and density of the bound interfacial surfactant layer and associated hydration shell were investigated using analytical ultracentrifugation for length and chirality purified (6,5) single-wall carbon nanotubes (SWCNTs) in three different bile salt surfactant solutions. The differences in the chemical structures of the surfactants significantly affect the size and density of the bound surfactant layers. As probed by exchange of a common parent nanotube population into sodium deoxycholate, sodium ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
120
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(123 citation statements)
references
References 61 publications
3
120
0
Order By: Relevance
“…The c(s) algorithm is a subset of the PCSA algorithm (horizontal line parameterization) and is a popular 1D approach which has previously been used for the analysis of NPs using constant ν¯p,italiceff and f/f 0 . 8, 14, 30, 31 For narrow PSDs, the c(s) analysis performs well if the correct ν¯p,italiceff is provided. Detailed results are given in the SI, Figure S9.…”
Section: Resultsmentioning
confidence: 99%
“…The c(s) algorithm is a subset of the PCSA algorithm (horizontal line parameterization) and is a popular 1D approach which has previously been used for the analysis of NPs using constant ν¯p,italiceff and f/f 0 . 8, 14, 30, 31 For narrow PSDs, the c(s) analysis performs well if the correct ν¯p,italiceff is provided. Detailed results are given in the SI, Figure S9.…”
Section: Resultsmentioning
confidence: 99%
“…In this process, the difference in the buoyancy and frictional force between nanotubes of varying lengths is exploited in order to achieve separation in a transient regime. According to Fagan et al [21,24], nanotubes with larger length have a lower frictional coefficient and tend to travel with less opposition to the centrifugal acceleration. Thus, longer length nanotube accumulates near the top of the centrifuge tube, when suspended in a density gradient fluid and subjected to an accelerating field, while the shorter ones tend to sediment deeper.…”
Section: Uv-vis-nir Spectroscopymentioning
confidence: 99%
“…The facial amphiphilic structure makes the BSs particularly suitable to exfoliate and disperse the latter nanostructures, avoiding aggregation and reboundling due to the strong π-π interactions among different nanotubes or graphene sheets. Some studies demonstrated that the packing density of natural BSs on specific types of single-walled CNTs (SWCNTs) [45] and their efficiency in exfoliating graphene [46] are dependent on the number of hydroxyl groups of the steroidal skeleton, highlighting their crucial role in the dispersion process. In particular, a comparative analysis of the interaction of NaC, NaDC and NaTC with (6,5) SWCNTs, showed that NaDC forms the thickest interfacial layer on the CNT surface, and NaTC the most densely packed [45].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Some studies demonstrated that the packing density of natural BSs on specific types of single-walled CNTs (SWCNTs) [45] and their efficiency in exfoliating graphene [46] are dependent on the number of hydroxyl groups of the steroidal skeleton, highlighting their crucial role in the dispersion process. In particular, a comparative analysis of the interaction of NaC, NaDC and NaTC with (6,5) SWCNTs, showed that NaDC forms the thickest interfacial layer on the CNT surface, and NaTC the most densely packed [45]. On the other hand, NaC and NaDC were used as dispersant of graphene nanosheets, and the absence of an OH group at the centre of the steroidal skeleton in NaDC was found to offer a flat and hydrophobic surface towards the graphene, which helps in the formation of uniform bilayer micelles on the carbon surface, thus making the exfoliation process more efficient [46].…”
Section: Accepted Manuscriptmentioning
confidence: 99%